Investigation and comparison on the interaction of laser and bio-tissue based on two classical models, the beam broaden model and diffusion approximation equation model, theoretically and experimentally - Cheng, Yuru; Shen, Yu; Gao, Yuxia; Wen, Ya; Lv, Ze; Wen, Ning; Wang, Erpeng; Li, Guanghe; Bo, Yong; Peng, Qinjun (Frontiers in Physics, 2024)
Three methods are used for a numerical solution, Monte Carlo method, diffusion approximation equation model and beam broaden model based on Beer-Lamberts law equation. The comparison between the first two methods is reported theoretically, and the latter is a better choice in the highdensity tissue. However, the comparison between the third method and the first or the second mothed is rarely reported. Two classical theoretical models describing the interaction during between laser and bio-tissue are analyzed and compared to determine which one is more suitable for analyzing the interaction, beam broaden model and diffusion approximation equation model. Intensity distribution is simulated and compared for the two models. Temperature distribution and thermal damage are investigated theoretically and experimentally for the both models. The differences and the reasons are analyzed. The diffusion approximation equation model is more suitable for analyzing the mechanism between the laser and the bio-tissue based on the degree of fitting between the simulated and experimental data. Theoretical analyses for the two models are carried out in detail. It's rarely reported the comparison between the two models, and it is reported in this article for the first time, theoretically and experimentally. This report provides a better choice for quickly analyzing the interaction mechanism between laser and bio-tissue.